Pathology - Schneider, Arthur S.; Szanto, Philip A. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
This revised fifth edition is an excellent pathology review for students preparing for the USMLE Step 1 and course examinations. Written in the popular Board Review Series outline format, this text covers general and basic pathology, major concepts of disease processes, and systemic pathology that surveys the principal disorders of each organ system through concise descriptions and full-color illustrations. USMLE-style questions at the end of each chapter emphasize board-relevant information and allow for self-testing to confirm strengths and uncover areas of weakness. Plus, the comprehensive exam at the end of the book is a great prep tool for the actual exam!
Cellular reaction to injury -- Inflammation -- Hemodynamic dysfunction -- Genetic disorders -- Immune dysfunction -- Neoplasia -- Environmental pathology -- Nutritional disorders -- Vascular system -- The heart -- Anemia -- Neoplastic and proliferative disorders of the hematopoietic and lymphoid systems -- Hemorrhagic disorders -- Respiratory system -- Gastrointestinal tract -- Liver, gallbladder, and exocrine pancreas -- Kidney and urinary tract -- Male reproductive system -- Female reproductive system and breast -- Endocrine system -- Skin -- Musculoskeletal system -- Nervous system -- Interpretation of diagnostic tests: laboratory statistics.
Includes index.
Keywords: Pathology -- Outlines, syllabi, etc; Pathology -- Examinations, questions, etc; Pathology -- Examination Questions; Examinations, questions, etc; Outlines, syllabi, etc; Aufgabensammlung